Sensitivity of ferromagnetic resonance in PdCo alloyed films to hydrogen gas. (15th March 2019) - Lueng, C.; Lupo, P.; Schefer, T.; Metaxas, P.J.; Adeyeye, A.O.; Kostylev, M.
Abstract: In this work we study the ferromagnetic resonance (FMR) response of Cox Pd1-x alloy samples with varying compositions (x = 0.65, 0.39, 0.24 and 0.14). We find significant differences in the FMR response of the samples to the presence of hydrogen gas in the samples' environment. Without any special processing, the films with x = 0.39 and 0.24 demonstrated behaviour which is promising for application in hydrogen gas sensing. Using FMR in the alloy thin films, we were able to measure hydrogen gas concentration in a very broad range - from 0.05% to 100%. Highlights: Ferromagnetic resonance (FMR) in PdCo alloy films was investigated in the presence of hydrogen gas. The FMR was shown to be sensitive to a broad range of concentrations of the gas. The sensitivity is non-vanishing from 0.05% to 100% of hydrogen in the environment.